Study on On-line Detection Method of Heavy Duty Truck Gearbox Assembly Quality based on Wavelet Analysis - Zheng Zou; Rupeng Cao; Qing Qu; Zhezhan Tang; Kangqu Zhou; Wei Chen (Jixie chuandong)
In order to determine the assembly quality of a certain type of gearbox， the common assembly faults of gearbox are briefly introduced based on the internal structure of gearbox， the characteristics frequencies of common faults of each gear and bearing in each gear position of gearbox are theoretically analyzed， an acoustic signal acquisition experimental platform is built and used to collect the acoustic signals of targeted gearbox in different gears. The collected signals are further processed through using the wavelet threshold de-noising method and then decomposed by using the wavelet analysis. Through spectral analysis of the corresponding frequency band signals and combining the results of theoretical analysis and experimental analysis， the assembly fault characteristics of the gearbox are obtained， which provides a basis for checking the assembly quality of the gearbox. This research has a certain reference significance for gearbox assembly quality detection.